Urban Community Perceptions and Experiences about Social Distancing During the Covid-19 Pandemic - Nugroho, Efa; Ningrum, Dina Nur Anggraini; Kinanti, Anastasia; Listianingrum, Devy; Sarifah, Mar’atul; Adeliani, Melia; Ulfah, Natijatul; Yuswantoro, Rico Novian (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Social distancing is a policy taken as a form of minimizing and suppressing the spread of Covid-19 which is increasing from time to time. The purpose of this study was to describe people's perceptions and experiences about social distancing during the Covid-19 pandemic. This research was a qualitative research with a phenomenological approach which was presented in a descriptive form. The location of this research was in Central Java Province. The method of data collection was carried out by in-depth interviews. The results showed that the respondents knew about social distancing well. Some respondents have applied social distancing in their daily lives. Information obtained on the behavior of sorting and choosing social distancing when in certain conditions and situations. Social distancing is applied when in public places and when meeting with strangers while when meeting with the closest people, social distancing is rarely applied. There was an attitude that appears when respondents meet perpetrators of social distancing policy violators, including letting them know, reprimand, advise, and set a good example. Most of the respondents have good knowledge of social distancing. The implementation of social distancing has been carried out in their daily lives, although it has not been comprehensive.